Legal Power of Authentic Deeds and Underhand Deeds in Civil Cases - Flora, Henny Saida (Jurnal Hukum dan Keadilan, 2025)
This study aims to analyze and compare the legal force between authentic deeds and deeds under hand in civil cases in Indonesia. The focus of the study is directed at how the two types of deeds function as written evidence in the evidentiary process in court, and the extent to which they provide legal certainty for the parties. The method used is normative legal research, which is research based on an analysis of legal norms in laws and regulations, legal doctrines, and court decisions. The approaches used include the statute approach, the conceptual approach, and the case approach. The results of the study show that authentic deeds made by public officials have perfect evidentiary power, both formally and materially, and provide higher legal certainty in the settlement of civil cases. Meanwhile, the deed under hand has a weaker evidentiary power because it relies on the acknowledgment of the parties who made it or reinforcement through legalization and additional proof. Therefore, to strengthen the legal position of deeds under hand, it is necessary to increase public legal literacy and update regulations that provide clarity regarding legalization and recognition of its evidentiary power before the law.